Compatibility Studies on Acacia tortilis and Zizyphus rotundifolia with Field Crops under Arid Conditions - Sharma, B. M.; Rathore, S. S.; Gupta, J. P. (Indian Forester, 1994)
The effect of growing pearlmillet and clusterbean crops in association with Acacia tortilis and Zizyphus rotundifolia on tree growth, crop yields, soil moisture and organic matter were ascertained for four consecutive years under arid conditions. The results revealed that the grain and straw yields of pearlmillet and clusterbean grown in association with trees decreased compared to sole crops. The reductions in yields under Acacia tortilis were more than Zizyphus rotundifolia. Clusterbean suffered greater reduction as compared to pearlmillet. Growth of trees was maximum in the control (Tree alone) while in association with the crops it decreased. Height increment in A. tortilis was more in association with clusterbean than that with pearlmillet while Z. rotundifolia attained greater height when in association with pearlmillet. Profile moisture stored at the time of crop harvest was maximum in sole crop of clusterbean and higher in clusterbean.Z. rotundifolia than clusterbean.A. tortilis. The organic matter content of soil after four years increased over the initial and followed the order: Clusterbean > Pearlmillet and Z. rotundifolia > A. tortilis.